An investigation of muscle strength, endurance and quality of life in South African children with haemophilia: a pilot study - Faris, DonnaTeresa (My University, 2011)
Haemophilia is an X-linked genetically transmitted disorder that is characterised by a deficiency in a circulating blood clotting factor (Falk et al 2000) and presents with intraarticular and intramuscular bleeding. Haemophilia A is the most common and results from a deficiency of clotting factor VIII (Barlow et al 2007). Haemophilia B results from a deficiency of clotting factor IX. Haemophilia A and B are described as having an incidence of approximately 1:10 000 and 1:60 000 people respectively (Engelbert et al 2007). Both haemophilia A and B are rare disorders, but are the most common, severe inherited bleeding disorder (Price et al 2007). The haemostatic defects of haemophilia lead to spontaneous and post-traumatic internal bleeding events (Von Mackensen et al 2004). Hilberg et al (2001) and Ghosh et al (2004) reported on the consequences of repeated bleeds and immobilization resulting in muscle atrophy, chronic synovitis, chronic haemophilic arthropathy, contractures, unequal leg lengths and loss of proprioception. Considering the musculoskeletal implications of haemophilia, Bradley et al (2006) reported that haemophilia may have a significant impact on the quality of life (QoL). Varni et al (2006) stated that children with chronic health conditions were reported to not only experience lower physical functioning, but also manifested lower emotional, social and school functioning in comparison with healthy children. The main aim of this study is to compare the muscle strength, endurance and QoL of a group of children with haemophilia to a group of aged matched healthy peers. Children between the ages of five and sixteen years were included in the study. The MicroFET 2 dynamometer has been used to assess the muscle strength of each subject and the Six Minute Walk Test has been used to test submaximal endurance levels of each group. The PedsQL is one of the quality of life assessment tools used to compare both groups, where the HAEMO-QOL has been used specifically to test the subjects with haemophilia. The first group of participants consisted of children having a diagnosis of haemophilia (n=15), and the second comparative group consisted of normally developing children (n=18). The results were analysed and compared using the student t-test and the Pearson’s correlation coefficient. The two groups were well matched for all anthropometric data. With regards to muscle strength, the haemophilia group showed significant weakness with regards to their left (L) elbow extensors and right (R) knee extensors in comparison to control group, with p values as p <0.01 and p< 0.05 respectively. In contrast the haemophiliac group showed significantly greater strength in the (L) and (R) ankle dorsiflexors, in comparison to the control group with p values as p<0.02 and p<0.00 respectively. No statistical significance was demonstrated in the 6MWT and QoL measures used between the two groups. The children with haemophilia in comparison to a healthy sample of age matched peers demonstrated almost equal abilities in measured muscle strength and submaximal endurance levels, and almost equal scores in the PedsQL of 75.5% and 77.7 % questionnaire indicating high perceived quality of life in both groups. There was a positive correlation between the Haemo-QoL questionnaire and the PedsQL questionnaire in the haemophilia group, indicating, again, high perceived quality of life with no discrepancies between the two questionnaires used. The findings of this study demonstrate a need for further research on haemophilic subjects in a South African context. However, the results have shown that both the groups in this present study have reduced muscle strength and poor endurance in comparison to international trends. With regards to perceived QoL, the boys with haemophilia had scores which were similar to those obtained in other studies.
Keywords: Hemophilia